Odpowiedź:
S(t) = t³ + 2t² - 3t [m]
t₀ = 0, t₁ = 1s, t₂ = 2s
v(t)=s(t)`
v(t)=3t²+4t+3
v₀=3m/s
v₁=3+4+3=10m/s
v₂=3*2²+4*2+3=12+8+3=23m/s
a(t)=v(t)`
a(t)=6t+4
a₀=4m/s²
a₁=6+4=10m/s²
a₂=6*2+4=16m/s²
b)
φ = t⁴ - 2t² +1 [rad]
t₀ = 0, t₁ = 1s, t₂ = 2s
ω(t)=φ(t)`
ω(t)=4t³-4t
ω₀=0
ω₁=4-4=0
ω₂=4*2³-4*2
ω₂=32-8=24 rad/s
a(t)=ω(t)`
a(t)=12t²-4
a₀=-4rad/s²
a₁=8rad/s²
a₂=12*2²-4=44rad/s²
c)
r=4m
S(t) = 2t² - 4t [m]
t₀ = 0, t₁ = 1s, t₂ = 2s
v(t)=s(t)`
v(t)=4t-4
v₀=-4m/s
ω₀=v₀/r=-4/4=-1rad/s
v₁=4*1-4=0
ω₁=0
v₂=4*2-4=4m/s
ω₂=4/4=1rad/s
a(t)=v(t)`
a(t)=4
a(t)=const
Wyjaśnienie: